2019
DOI: 10.1002/acr.23792
|View full text |Cite
|
Sign up to set email alerts
|

Azathioprine and Mycophenolate Mofetil Adherence Patterns and Predictors Among Medicaid Beneficiaries With Systemic Lupus Erythematosus

Abstract: Objective. Azathioprine (AZA) and mycophenolate mofetil (MMF) are immunosuppressants frequently used in the treatment of moderate-to-severe systemic lupus erythematosus (SLE). We studied longitudinal patterns and predictors of adherence to AZA and MMF in a nationwide US SLE cohort.Methods. In the Medicaid Analytic eXtract (2000-2010) database, we identified patients with SLE who initiated AZA or MMF (no use in the prior 6 months) with ≥12 months of continuous follow-up. We dichotomized adherence at 80%, with ≥… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 15 publications
4
35
0
1
Order By: Relevance
“…In this vulnerable population of patients with SLE among whom only 15% were adherent to HCQ treatment over the first year of use, we observed significant relationships between individual and contextual factors and adherence. Although it is challenging to compare across studies given differences in populations (e.g., academic‐based cohorts versus public insurance beneficiaries) and in adherence measures (e.g., self‐reported surveys versus claims‐based prescription refill data), our findings were similar to estimates of adherence to other SLE‐related medications in the Medicaid population (). In line with prior studies, younger age, black race, Hispanic ethnicity, and antidepressant use were associated with poorer adherence ().…”
Section: Discussionsupporting
confidence: 54%
“…In this vulnerable population of patients with SLE among whom only 15% were adherent to HCQ treatment over the first year of use, we observed significant relationships between individual and contextual factors and adherence. Although it is challenging to compare across studies given differences in populations (e.g., academic‐based cohorts versus public insurance beneficiaries) and in adherence measures (e.g., self‐reported surveys versus claims‐based prescription refill data), our findings were similar to estimates of adherence to other SLE‐related medications in the Medicaid population (). In line with prior studies, younger age, black race, Hispanic ethnicity, and antidepressant use were associated with poorer adherence ().…”
Section: Discussionsupporting
confidence: 54%
“…In order to investigate whether patterns of adherence are distinct by drug, we have separately used group-based trajectory models to examine adherence to azathioprine and mycophenolate mofetil also within the Medicaid SLE population. (39) Interestingly, while we similarly noted poor nonadherence to both drugs with fewer than 20% of individuals characterized as adherent to either drug, we found that each drug had a pattern of adherence that differed from that of HCQ. While both drugs had subsets of the population who were persistent adherers and persistent nonadherers, the paths of the intermediate nonadherers were distinct.…”
Section: 4 Discussionsupporting
confidence: 51%
“…A literature review of medication utilisation in SLE found the percentage of non-adherent patients ranged from 43% to 75%, with studies consistently reporting that >50% of patients were non-adherent 28. Studies of specific SLE treatments, many of which are considered the cornerstone of SLE treatment (hydroxychloroquine, azathioprine, mycophenolate mofetil and immunosuppressive medications), have also consistently shown adherence rates of <25% and medication possession ratios well below the accepted threshold of 80% 29–32. Adherence may have been suboptimal due to hospitalisation as belimumab treatment may have been suspended.…”
Section: Discussionmentioning
confidence: 99%